Kujang And Batik Bogor Educational Games To Grow Millennial Generation Enthusiasm For Local Wisdom Through Digital Media - Eneng Tita Tosida (International Journal of Business, Economics, and Social Development, 2020)
Educational game is a game that raises local wisdom in which there are values of local wisdom that can be remembered and implemented by users in everyday life. in this educational game made in accordance with the rules needed in the world of education. starting from the elements of game design and techniques used in making games. This application was built using MDLC (Multimedia Development Live Cycle) combined with FSM (Finite State Machine) so that this educational game is very easy to understand and understand by users, especially millennial generation. after the socialization to the millennial generation there was an increase in understanding of the local wisdom of Bogor, especially the Kujang and the batik of Bogor.